Acceptance of Global Positioning System (GPS) Technology Among Dementia Clients and Family Caregivers. Issue 2 (3rd April 2017) - Liu, Lili; Miguel Cruz, Antonio; Ruptash, Tracy; Barnard, Shannon; Juzwishin, Don
ABSTRACT: The purpose of this study was to examine the acceptance of Global Positioning System (GPS) used to help people with dementia, who are at risk for wandering in their communities. We used a mixed methods research approach that included use logs, pre and post paper-based questionnaires, and focus groups. Forty-five client-caregiver pairs (dyads) were included to use one of the GPS devices for an average of 5.8 months over a 1-year period. GPS acceptance was high; dyads were likely to continue using the GPS. According to the participants, the GPS provided caregivers peace of mind and reduced anxiety in dyads when clients got lost.